Efficacy and safety of lebrikizumab for the treatment of moderate-to-severe atopic dermatitis: a systematic review and meta-analysis - Lin, Jinger; Luo, Min; Zhuo, Qianwei; Chen, Nuo; Zhang, Haosong; Han, Yue (Frontiers in Pharmacology, 2024)
Background: Lebrikizumab, an IL-13 immunomodulator, has shown recommendable effectiveness and safety in clinical studies for the treatment of moderate-to-severe atopic dermatitis (AD) in adolescents and adults.Objective: To explore the efficacy and safety of lebrikizumab in the treatment of moderate-to-severe AD by meta-analysis.: PubMed, Embase, Web of Science, Medline and ClinicalTrials.gov databases were searched through August 8, 2023. Randomized clinical trials of treatment with lebrikizumab for moderate-to-severe AD were included screening titles, abstracts and papers. Results: A total of five studies involving 1551 patients with AD were identified. Pooled analysis revealed significant improvements in Eczema Area and Severity Index score (SMD = -0.527; 95% CI = [-0.617,-0.436]), Investigator's Global Assessment score (RR = 2.122; 95% CI = [1.803,2.496]), Body Surface Area score (SMD = -0.608; 95%CI = [-1.099,-0.118]), SCORing Atopic Dermatitis score (SMD = -0.441; 95%CI= [-0.633,-0.250]), Pruritus Numeric Rating Scale score, Patient-oriented Eczema Measure scores, Sleep-loss Likert scale score and Dermatology Life Quality Index scores showed similar results. Adverse events (RR = 0.984;95% CI=[0.907,1.068]) for lebrikizumab showed no statistically significant difference to placebo and were the same as serious adverse events (RR = 0.748;95% CI=[0.410,1.364]).This meta-analysis showed that lebrikizumab has higher efficacy and safety in the treatment of moderate-to-severe AD and the 250 mg Q2w dosage regimen appears to be more advantageous.